FAKTOR YANG MEMPENGARUHI TINGKAT FOREIGN DIRECT INVESTMENT DI NEGARA G20 - Pentagona Putri, Rengginas; Yuniarti, Dini; Khoirudin, Rifki (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the influence of Gross Domestic Product (GDP), Labor, Exchange Rate, Trade Openness, and Inflation on Foreign Direct Investment (FDI) in 10 G20 countries. The data used are panel data obtained from UNCTAD and the World Bank for the period 2013–2022. The analytical method applied is panel data analysis using the Seemingly Unrelated Regression (SUR) approach with the help of Stata14 software. The results show that Trade Openness and Inflation do not have a significant effect on FDI. The Labor variable has a significant positive effect, indicating that an increase in labor can encourage FDI inflows. Meanwhile, GDP and Exchange Rate have a significant negative effect on FDI in the 10 G20 countries, suggesting that rising GDP and a weakening exchange rate may reduce foreign investor interest.